Penggunaan model pembelajaran quick on the draw untuk meningkatkan keterampilan berpikir fluency pada pembelajaran IPS kelas iv sekolah dasar - Septi Indriyani (Didaktika Dwija Indria, 2019)
This research was a classroom action research which aimed to improve fluency thinking skills in Social Sciences lessons through used Quick on The Draw learning model for 4th grade of elementary school student at Surakarta on 2018/2019 academic year. The subjects of this research were class teacher and 28 students from 4th grade of elementary school student. The procedure of this research consisted of 3 cycles, each of that cycles had 4 stages, namely planning, action, observation, and reflection. Data collection of this research was done by interviewing, observing, fluency thinking skills tests, and document studies technique. Data validity used is content validity and triangulation technique. This research used interactive analysis (Miles and Huberman models) for data analysis. The results of the research after the action increased from initial condition was 65.68 (39%) to 78.46 (61%) in the first cycle, 87.21 (75%) in the second cycle, and 92.36 (86%) in the third cycle. Based on the results of this research, it was concluded that the fluency thinking skills of 4th grade elementary school students in social science leasson increased after the Quick on The Draw learning model was implemented.       Keywords: fluency thinking skills, social sciences lessons, Quick on The Draw learning model, elementary school